1998
DOI: 10.1002/(sici)1099-078x(199802)13:1<1::aid-bin1>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of token reinforcement and response cost on the accuracy of spelling performance with middle‐school special education students with behavior disorders

Abstract: The effects of token reinforcement and response cost on the accuracy of spelling performance with three adolescent special education students were examined. A multiple‐baseline design across students was used to evaluate the effects of token reinforcement and response cost intervention. A greater percent of accuracy on daily spelling exams was obtained during the token reinforcement plus response cost condition than during the baseline condition. This was replicated for each student. Follow‐up data collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
0
5
1
1
Order By: Relevance
“…This system, free of many of the negative side effects of punishment, has been employed as a procedure to control a variety of inappropriate behaviours in classroom settings (Iwata & Bailey, 1974;Kazdin, 1972;McCain & Kelley, 1994). Some studies have demonstrated that token reinforcement (positive reinforcement) and response cost is a more effective package to increase academic behaviour than token reinforcement alone (McLaughlin & Malaby, 1977;Truchlicka, McLaughlin, & Swain, 1998). However, in our study children did not show any advantage of condition "þ/2" compared to condition "þ" (Experiment 2).…”
Section: Discussioncontrasting
confidence: 80%
“…This system, free of many of the negative side effects of punishment, has been employed as a procedure to control a variety of inappropriate behaviours in classroom settings (Iwata & Bailey, 1974;Kazdin, 1972;McCain & Kelley, 1994). Some studies have demonstrated that token reinforcement (positive reinforcement) and response cost is a more effective package to increase academic behaviour than token reinforcement alone (McLaughlin & Malaby, 1977;Truchlicka, McLaughlin, & Swain, 1998). However, in our study children did not show any advantage of condition "þ/2" compared to condition "þ" (Experiment 2).…”
Section: Discussioncontrasting
confidence: 80%
“…ClassDojo includes a function to add points to reinforce positive behaviors, but it also allows a user to take away earned points. Withdrawing points or tokens earned by students can change a token economy into a blended system that incorporates response cost (Truchlicka, McLaughlin, & Swain, 1998). Response cost is a behavioral procedure in which a stimulus that has been awarded, in this case a point, is removed with the goal of decreasing (i.e., punishing) the occurrence of an inappropriate behavior.…”
Section: Response Costmentioning
confidence: 99%
“…Among the most frequently cited examples of behavior-management strategies are the good-behavior board game (Cipani, 2007;Infantino & Little, 2005), behavioral contracting (Roberts, White, & McLaughlin, 1997), incident barometer programs (Truchlicka, McLaughlin, & Swain, 1998), in-class time-out (Yeager & McLaughlin, 1995), removal from classroom time-out (Algozzine & Kay, 2002), positive compliance (Ardoin, Martens, & Wolfe, 1999), beeper systems (Henderson, Jenson, & Erken, 1986), backup reinforcers (Zarcone, Fisher, & Piazza, 1996), the goodstudent game (Babyak, Luze, & Kamps, 2000), negative reinforcement (Pfiffner & O'Leary, 1987), token economies (Lucker & Molloy, 1995), and reinforcement and punishment (Little, Hudson, & Wilks, 2002). Although research has examined both teachers' and students' attitudes to the effectiveness of different incentives and deterrents (see Infantino & Little, 2005), what has not been explored is whether some aspects of these strategies are only partially effective in the desired direction, sometimes having the reverse effect and actually assisting young people at risk to achieve their goals of establishing a nonconforming social identity among their peers.…”
Section: Using Behavior-management Systems To Enhance Reputationsmentioning
confidence: 99%